Strategi Pengelolaan Kawasan Permukiman Kumuh di Kota Gorontalo - Irfan; H. Baruwadi, Mahludin; Rahim, Sukirman (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
The study aims at analysing the management strategy of slums areas. In addition, this study is carried out in all slums in Gorontalo City. The techniques and procedures employed in this study are survey, FGD (Focus Group Discussion), and interview. At the same time, the analysis method is done by applying a quantitative approach, where the analysis for scoring the aspects of slum levels referring to the Regulation of the Minister of Public Works and Housing (PUPR) Number 14 of 2018, the measurement of priority aspects in handling slums using AHP (analytic hierarchy process) analysis, and management strategy applying SWOT analysis. Finding reveal that 1) the slum level in Gorontalo City is in the light slum category with the biggest problem is Drainage for 42% and the slightest problem is potable water for 23%, 2) the priority aspect in handling slum are potable water for 42,25%, 3) the management strategies of slum area are performed by enhancing collaboration between regional and central programs with the provision complete supporting documents to meet technical planning criteria that have good quality, improving the role of Housing and Settlement Working Group (POKJA PKP) in supporting program coordination, advocacy of Regional Working Unit and stakeholders in Gorontalo City, and providing strategic inputs proposing a planning budget for slum area management. In addition, the management strategy is carried out by preparing planning documents for the handling of slums that are integrated with other planning documents and increasing the role of social institutions in the community in supporting the handling of slums.